Levels of Evidence Supporting the North American and European Perioperative Care Guidelines for Anesthesiologists between 2010 and 2020: A Systematic Review. (July 2021) - Laserna, Andres; Rubinger, Daniel A.; Barahona-Correa, Julian E.; Wright, Noah; Williams, Mark R.; Wyrobek, Julie A.; Hasman, Linda; Lustik, Stewart J.; Eaton, Michael P.; Glance, Laurent G.
Abstract : Background: Although there are thousands of published recommendations in anesthesiology clinical practice guidelines, the extent to which these are supported by high levels of evidence is not known. This study hypothesized that most recommendations in clinical practice guidelines are supported by a low level of evidence. Methods: A registered (Prospero CRD42020202932) systematic review was conducted of anesthesia evidence-based recommendations from the major North American and European anesthesiology societies between January 2010 and September 2020 in PubMed and EMBASE. The level of evidence A, B, or C and the strength of recommendation (strong or weak) for each recommendation was mapped using the American College of Cardiology/American Heart Association classification system or the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. The outcome of interest was the proportion of recommendations supported by levels of evidence A, B, and C. Changes in the level of evidence over time were examined. Risk of bias was assessed using Appraisal of Guidelines for Research and Evaluation (AGREE) II. Results: In total, 60 guidelines comprising 2, 280 recommendations were reviewed. Level of evidence A supported 16% (363 of 2, 280) of total recommendations and 19% (288 of 1, 506) of strong recommendations. Level of evidence C supported 51% (1, 160 of 2, 280) of all recommendations and 50% (756 of 1, 506) of strong recommendations. Of all the guidelines, 73% (44 of 60) had a low risk of bias. The proportion of recommendations supported by level of evidence A versus level of evidence C (relative risk ratio, 0.93; 95% CI, 0.18 to 4.74; P = 0.933) or level of evidence B versus level of evidence C (relative risk ratio, 1.63; 95% CI, 0.72 to 3.72; P = 0.243) did not increase in guidelines that were revised. Year of publication was also not associated with increases in the proportion of recommendations supported by level of evidence A (relative risk ratio, 1.07; 95% CI, 0.93 to 1.23; P = 0.340) or level of evidence B (relative risk ratio, 1.05; 95% CI, 0.96 to 1.15; P = 0.283) compared to level of evidence C. Conclusions: Half of the recommendations in anesthesiology clinical practice guidelines are based on a low level of evidence, and this did not change over time. These findings highlight the need for additional efforts to increase the quality of evidence used to guide decision-making in anesthesiology. Abstract : In a systematic review of 2, 280 recommendations in 60 guidelines published by major North American and European societies, half of the recommendations were supported by a low level of evidence. The proportion of recommendations supported by a high level of evidence did not increase between 2010 and 2020.